Contribution Of Resistance Muscle Power Arm And Hand-Eye Coordination On The Passing Skills Students Volleyball Sports Education Department State University Faculty of Sport Science Padang - Astuti, Yuni (JPI (Jurnal Pendidikan Indonesia), 2017)
Â The problem in this research is still many students are less capable of passing on volleyball. This study aims to determine the contribution of the arm muscle strength endurance and hand-eye coordination against passing on volleyball skills. This type of research is correlational. The population in this research that students who take courses in basic volleyball as many as 142 people. Purposive sampling technique. The number of samples in this study were 30 people. To measure the strength of arm muscle endurance using a push-up tests, and eye-hand coordination using Und-Fangen Ballwerfen Test. And passing skills on using top passing skills tests. Data were analyzed by product moment correlation and followed with a double. The result showed that 1) the contribution of the arm muscle strength endurance against passing on volleyball skills, namely 15%. 2) contribution to the hand-eye coordination skills of passing on volleyball is 22%. 3) the contribution of the arm muscle strength endurance and hand-eye coordination jointly against passing on volleyball skills is 30%.